Visual and sensory outcomes after refractive surgery for pediatric anisometropia - Ahmed A. Farrag; Mahmoud A.B. Mohamed; Hasan S. Yousef (Al-Azhar Assiut Medical Journal)
Background and aim Amblyopia is one of the most common causes of loss of vision in children. Unfortunately, in high pediatric anisometropia, spectacle correction is not tolerated by many children. Also, contact-lens wear by children may seem to be extremely challenging, difficult, and unrewarding. So, the aim of this study is to evaluate visual and sensory outcomes after refractive surgery for pediatric anisometropia resistant to conservative treatment. Patients and methods A prospective nonrandomized clinical study was carried out on 56 eyes of 56 children with anisometropia resistant to usual treatment. Refractive surgery was conducted and according to its type, the included patients were divided. Laser In Situ Keratomileusis (LASIK) group included 26 patients, while Photorefracive Keratectomy (PRK) group included 15 children besides 15 patients in implantable collamer lens (ICL) group. Complete ophthalmologic examination was performed before and after surgery for all groups with follow-up visits at 1, 3, 6, 12, and 18 months. Results Uncorrected Visual Acuity (UCVA), Best Corrected Visual Acuity (BCVA), and refractive parameters improved dramatically in all groups with more significant improvement in LASIK group in comparison with the other groups. However, the preservation of BCVA was better with the ICL at both immediate healing period and through the 18-month follow-up. Sensory tests did not show significant changes in all groups. Conclusion Refractive surgery is safe and effective for pediatric anisometropia treatment. LASIK has better visual outcomes and ICL has more preserved outcomes.